Does Facebook 'threaten' romantic relationships? Online surveillance and couple visibility behaviours in romantic jealousy and couple relationship quality in a sample of Italian women. Issue 2 (4th March 2023) - Imperato, Chiara; Everri, Marina; Mancini, Tiziana
ABSTRACT: Facebook has been identified as one of the most influential social network site (SNS) in the formation, maintenance and interruption of romantic relationships. Over the last decade, several studies have been carried out on Facebook and romantic relationships; however, there is still lack of evidence on how the reciprocal perceptions of partners' behaviours on Facebook relate with couple relationship quality. This study aimed to fill this gap examing whether and to what extent participants' surveillance and visibility behaviour related with the perception of their partner's surveillance and visibility behaviour, and to what extent this perception related with both romantic jealousy and relationship quality. A sample of 635 heterosexual women having a romantic relationship participated in a study, which consisted of answering an online questionnaire with items on both the participants' and their partner's online behaviour. Path analyses were used for testing the hypotheses. Results showed that Facebook supported behaviours that can affect the quality of romantic relationship. Contrary to what expected, both online surveillance and couple visibility positively related with romantic jealousy, which in turn mediated the relation between surveillance and relationship quality, thereby worsening the participants' perception of couple relationship quality.